Estudo do desempenho de um motor de combustão interna turboalimentado e com restrição da entrada de ar - Fortuoso, Marcelo (2021)
The present work describes the performance and efficiency improvement achieved in an engine that will be used in the Formula SAE competition. It is an engine manufactured by the Yamaha company, with 320 cc of displacement, 2 cylinders and 4 valves per cylinder. In its original version, the engine is naturally aspirated and fueled with gasoline, and the maximum power and maximum torque values declared by the manufacturer are, respectively, 42 hp and 3.02 kg.f.m. The increase in power and torque of this engine was obtained by using a turbocharger with an intercooler and by replacing gasoline with ethanol. Such modifications were made observing a limitation established in the Formula SAE competition rules, according to which the intake air must pass through a 19 mm diameter throat, thus restricting the maximum amount of air that can be admitted. After the modifications, the engine was recalibrated using the Megasquirt MS2 programmable electronic injection system to then be mounted on an experimental vehicle, which was subjected to tests in a roller dynamometer. In addition, a computational model was built using the Ricardo Wave software, which allowed simulating the functioning of the engine before and after the modifications. The simulation results were compared with experimental results, which allowed validating the simulation results and verifying that the power and torque gains reached values in the order of 70% at their peak values.